11-14 Year-Old Male Athletes and Non-Athletes' Probability to Get Ankle Sprain - Marius Bražulis; Gražina Krutulytė (Lithuanian Sports University, 2020)
Popularization various sports in Lithuania encourages children to start professional sports career. Therefore, the number of sports injuries increases inevitably, and it has almost reached the number of the developed countries. Young athletes are more vulnerable than pre-pubertal children, whereas the increased amount of Androgens causes the increase in weight, speed and strength [1]. It has been argued that poor balance is a lower limb injury risk factor [11, 16]; and during puberty there is a temporary decrease in coordination and balance [7] which can cause significant injuries in children. The aim of research: to identify 11-14 year-old football, basketball, volleyball players, gymnasts and the Eastern martial arts athletes and non-athletes' probabilities to get ankle sprain. The objectives of research: 1. Evaluate 11-14 year-old football, basketball, volleyball players, the gymnasts and the Eastern martial arts athletes and non-athletes' probability to get ankle sprain in the right and left legs. 2. Identify which sport has the highest probability to get ankle sprain. 3. Identify if ankle sprain of the past affects the possibility of repeated injury. The study subjects were 110 random selected 11-14 year-old athletes and non-athletes, 28 of which have had of ankle ligament injury. The study was conducted in the main Zaliakalnio school Kaunas, Kaunas center sports school and the "Tornado" basketball school in 2008-2009. The study measured the leg length, and the modified stars excursion balance test determined young athletes and non-athletes' probability to get ankle sprain. Conclusions: 1. Found that 80% of non-athletes, 11-14 year-old boys demonstrated the probability of the right and 70% left ankle injuries, basketball players: 85% of right and 70% left ankle injuries, volleyball players: 70% right and 75% left ankle injuries, football players: 50% right and 30% left ankle injuries, the Eastern martial arts athletes: 30% right and 50% left ankle injuries, gymnasts: 10% right and 10% left ankle injury. 2. The greatest probability to get ankle sprain are for basketball, volleyball players and non-athletes 11-14 year-old boys. 3. Ankle injuries of the past affect the re-injury (p < 0.01). Keywords: star excursion balance test, ankle ligaments injury, sport injuries.